THE INFLUENCES OF SOMALI PIRACY AS INTERNATIONAL RELATIONS ACTOR (Study Case: Somali Piracy in Gulf of Aden 1991-2008) - Iis Istianah Baedlowie (2011)

(untitled)
This undergraduate thesis has an aim in giving an explanation about the case influences of Somali Piracy as international relations actor study cases Somali Piracy in Gulf of Aden in 1991 - 2008. This thesis analyzes the Somali piracy problem in the Gulf of Aden focusing specifically on Somali pirate networks and its influences. It provides an historical background of piracy itself the political unrest in Somalia and the subsequent government collapse that followed in an attempt to identify t